(untitled) (Global Media Journal - German Edition, 2021)
Voicing systematically marginalised communities is a problem historically posed in the media and communications field, in terms of de-Westernisation and, more radically, cosmopolitanism. Such a problem has been magnified in the COVID-19 pandemic, with narratives from systematically devoiced communities – ranging from migrants to informal workers, ethnic minorities, economically poor people, and survivors of domestic violence – remaining untold. Recognising the need for a conceptual apparatus to voice the silenced narratives of the pandemic, this paper conducts two tasks: first, it crafts a theoretical apparatus of three devices (data at the margins; data poverty; and the datafication of anti-poverty programmes) to conceptualise COVID-19 stories from the margins. Second, it applies such a theoretical apparatus to a map of five problems (counting in the pandemic; new inequalities and vulnerabilities; datafied social protection; data injustices; solidarity and resistance from below) opened by discussion on COVID-19 from the margins. By doing so it offers a conceptual lens responding to the call for cosmopolitanism in media and communications, applying it to the study of COVID-19 narrations from the globe.